Reklamasi Lahan Pascapenambangan Batubara Menggunakan Biochar Dan Penanaman Mucuna - Roby (Jurnal Loupe, 2017)
Abandoned mining site is a place that can be used a plantation area or fish cultivation which could greatly benefit the surrounding community. In general, vegetation cannot easily grow in former area of coal deposit for years. Nevertheless, this is not the case with the advanced biotechnology at hand. This research aimed to identify former area of coal deposit that can be used for agriculture and plantation. The investigation went for five months from May 2017 to October 2017 PT coal mining area. BBE Tana Datar, Muara Badak Sub-district, Kutai Kartanegara. The design used in this research was Randomized Block Design in Factorial form where the first factor was biochar and the second factor was mucuna.The first factorswere, B1 (without biochar), control B2 (Biochar 25 kg), B3 (Biochar 50 kg), B4 (Biochar 75 kg), B5 (Biochar 100 kg) in each bed. the second factors were(M1 Mucunaplanted 20 cm x 20 cm and M2 (Mucuna planted 30 cm x 30 cm). The findings conclude that land reclamation at fomer coal mining area with the provision of biochar and mucuna planting is possible even at a low cost and it is also environmental friendly. This enables the area to be utilized for agriculture and plantation.